Determination of Flavonoid and Caffeine Content in Black and Oolong Teas - Zayadi, Rabiatul Adawiyah; Abdul Rahim, Nurliyana; Abu Bakar, Faridah (Journal of Science and Technology, 2016)
The world is blessed with tea for its health benefits and the hundreds of flavours to be chosen from. Flavonoid and caffeine is the most abundant type of phenolic compound and alkaloid found in tea respectively. These compounds can be extracted using various solvents, resulting in various concentration when compared with water as the solvent. This study was conducted by preparing tea infusion from both distilled water and organic solvents to observe the effect of solvents on the content of flavonoid and caffeine. Using spectrophotometric method, the content of flavonoid and caffeine in commercial black (Boh, Sabah, Lipton) and oolong (Oo Long Kee Zhong, Montea, Ten Ren) teas obtained from Malaysian market were determined. Sabah and Montea has the highest flavonoid (0.044 g/L) and caffeine (3.585 g/L) content in distilled water respectively. The final content of flavonoid and caffeine was found to be higher in organic solvents compared to distilled water, as well as when the steeping time is increased.